Improving the Outcomes of Clinically Deteriorating Patients: Evaluating and Supporting the Practice Needs of Multidisciplinary Teams - Berlingeri, Jacinta (Curtin University, 2022)
Recognising and responding to patient deterioration is problematic throughout the world. A descriptive, exploratory study was designed to understand the issue from tertiary hospital medical and surgical ward perspectives. The results of a literature review, medical record audit and clinician survey were used to develop a framework for multidisciplinary, in situ simulation scenarios, to be used by facilitators to design simulations to improve the recognition, response, and appropriate escalation of deteriorating patients.